Fear and Anxiety in the Arab World - Amber Haque (International Institute of Islamic Thought, 2004)
The title is certainly catchy, as not much has been written on fears and anxieties in the Arab world. Much, however, has been written on Muslims and Islam post-9/11. While some writers genuinely try to understand the various Islamic ideologies and Muslim cultures, others seek to paint a rather dim and depressing picture of Muslim societies. This book attempts to describe Arabs, as well as their fears and anxieties, in the garb of “interdisciplinary research.” It is divided into seven chapters and contains a section on notes, a bibliography, and an index. The chapters address issues related to Arab politics (e.g., political identity, nationalism, and minority issues) and more general areas (e.g., religion and Arab culture). The author is a professor of political science and diplomacy at the Notre Dame University in Lebanon. In the preface and opening chapter, Nehme introduces the growing field of political psychology, which draws upon various psychological theories to interpret human political behavior. Although he admits that the best results can be obtained through collaborative research between experts in each discipline, he dares to make an independent attempt to analyze Arab fears and anxieties from a Freudian perspective. The book’s first few pages are quite a turn-off, as many preposterous statements are made. Playing psychologist, Nehme asserts that world events are themselves natural experiments and, therefore, his assumptions are “empirically based” (p. 2). He diagnoses the problem of violence among Arabs as resulting from a “built-in consistency of anxiety” (p. 3), “most Arabs no longer appeal to God … instead, they call on their governments for relief” (p. 4), “they are afraid of everything” (p. 7), “Arab men are afraid that their wives will be sexually attracted to other men if they leave home to work” (p. 8), and so on. He goes on to characterize suicidal tendencies among Arabs as a “death wish” that is not new in Arab history, as it develops their inner power … through acquiring weapons, and states ...